Association of water intake and hydration status with risk of kidney stone formation based on NHANES 2009–2012 cycles. Issue 9 (6th September 2022) - Wang, Jie-Sian; Chiang, Hsiu-Yin; Chen, Hung-Lin; Flores, Martha; Navas-Acien, Ana; Kuo, Chin-Chi
Abstract: Objective: Evaluating the association of water intake and hydration status with nephrolithiasis risk at the population level. Design: It is a cross-sectional study in which daily total plain water intake and total fluid intake were estimated together with blood osmolality, urine creatinine, urine osmolality, urine flow rate (UFR), free water clearance (FWC) and urine/blood osmolality ratio (Uosm :Bosm ). The associations of fluid intake and hydration markers with nephrolithiasis were evaluated using multivariable logistic regression. Setting: General US population. Participants: A total of 8195 adults aged 20 years or older from the National Health and Nutritional Examination Survey 2009–2012 cycles. Results: The population medians (interquartile ranges, IQR) for daily total plain water intake and total fluid intake were 807 (336–1481) and 2761 (2107–3577) ml/d, respectively. The adjusted OR (95 % CI) of nephrolithiasis for each IQR increase in total plain water intake and total fluid intake were 0·92 (95 % CI 0·79, 1·06) and 0·84 (95 % CI 0·72, 0·97), respectively. The corresponding OR of nephrolithiasis for UFR, blood osmolality, Uosm :Bosm and urine creatinine were 0·87 (95 % CI 0·76, 0·99), 1·18 (95 % CI 1·06, 1·32), 1·38 (95 % CI 1·17, 1·63) and 1·27 (95 % CI 1·11, 1·45), respectively. A linear protective relationship of fluid intake, UFR and FWC with nephrolithiasis risk was observed. Similarly, positive dose–response associations of nephrolithiasis risk with markers of insufficient hydration were identified. Encouraging a daily water intake of >2500 ml/d and maintaining a urine output of 2 l/d was associated with a lower prevalence of nephrolithiasis. Conclusion: This study verified the beneficial role of general water intake recommendations in nephrolithiasis prevention in the general US population.